Comparative Analysis of Textbooks of Moral Beliefs Class VII MTs Between the 2013 Curriculum and the Independent Curriculum - Nurhibatulloh, Rifqi; Tumin, Tumin (Jayapangus Press, 2025)
Changes in national curriculum policies require substantial adjustments to the quality and relevance of textbooks as the main means of learning. This study aims to analyze comparatively the textbook of Moral Faith class VII Madrasah Tsanawiyah which is used in the 2013 Curriculum (K13) and the Independent Curriculum (IKM). The research was conducted with a qualitative approach through a literature study of two textbooks, using a multicomponent approach that includes five main aspects: content, language, presentation, thematic concepts, and evaluation. The results of the study show that K13 books are conceptual and memorization-oriented with a linear approach, while IKM books are more contextual, communicative, and support active learning through the integration of character values and digital features such as QR codes. IKM books also show excellence in presenting materials that are relevant to students' lives and supporting the development of 21st century skills. The conclusion of this study emphasizes that the Independent Curriculum book is more responsive to the needs of modern students and more effective in supporting the internalization of the values of faith and morals. These findings contribute to the development of religious textbooks as evaluation and reference materials in designing learning materials that are integrative, applicative, and in line with the spirit of the latest curriculum-based character education.